Electroanalytical Methods 2009
DOI: 10.1007/978-3-642-02915-8_13
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Quartz Crystal Nanobalance

Abstract: The method of piezoelectric microgravimetry (nanogravimetry) using an electrochemical quartz crystal microbalance (EQCM) or nanobalance (EQCN) can be considered as a novel and much more sensitive version of electrogravimetry. The EQCN technique has become a widely used technique in several areas of electrochemistry, electroanalytical chemistry, bioelectrochemistry, etc. [1][2][3][4][5][6][7][8][9][10]. Obviously, mass changes occurring during adsorption, sorption, electrosorption, electrodeposition, or spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The use of EQCA as an important analytical technique has advanced considerably during the last two decades and has been successfully used for studying a variety of the processes occurring with coated QCs in different media . The outstanding contributions of several research groups should be specially acknowledged and is documented in some review articles . However, viscoelastic models, valid for various polymeric coatings, are not suitable to describe charging processes in composite intercalation electrodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of EQCA as an important analytical technique has advanced considerably during the last two decades and has been successfully used for studying a variety of the processes occurring with coated QCs in different media . The outstanding contributions of several research groups should be specially acknowledged and is documented in some review articles . However, viscoelastic models, valid for various polymeric coatings, are not suitable to describe charging processes in composite intercalation electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…[ 16,17 ] The outstanding contributions of several research groups should be specially acknowledged and is documented in some review articles. [ 18,19 ] However, viscoelastic models, [ 20 ] valid for various polymeric coatings, are not suitable to describe charging processes in composite intercalation electrodes. Here we rely instead on our previous work devoted to hydrodynamic spectroscopy of chemically and structurally non-homogeneous composite electrode coatings (see ref.…”
Section: Hydrodynamic Spectroscopy Of Ti 3 C 2 T X Composite Electrodmentioning
confidence: 99%
“…The amount of the electrodeposited PEDOT layer can be estimated using the Sauerbrey equation [30], which relates the frequency change (∆f ) of the crystal resonator with the amount of deposited mass (∆m):…”
Section: Electrochemical Preparation and Characterization Of Pedot-aumentioning
confidence: 99%
“…As in the case of HCOOH, oscillations in E and Δm are out-of-phase for both applied currents, corroborating thus the qualitative features discussed. Inzelt and coworkers 23,[50][51][52] studied the potential and mass variations in the oscillatory electro-oxidation of formic acid and 2-propanol on platinum. In both cases, the authors found that the E/t and Δm/t relationships are out-of-phase, as in the present case.…”
Section: Oscillatory Electro-oxidation Of Hcooh On Pt and On Au/pani/...mentioning
confidence: 99%